“Mediterranean Diet ‘reflections’”. Estimating adherence to the Mediterranean diet through secondary data - Finardi, Corrado; Bucchini, Luca; Turrini, Aida (Progress in Nutrition, 2018)
Purpose: to compare several countries against many Mediterranean adherence indices, calculated by looking at 19 European Member States. The value of a population-level Mediterranean Diet Index, the Mediterranean Adequacy Index (P-MAI) is at the core of the analysis. Design/methodology/approach: the EFSA’s Concise European Food Consumption Database (mean g/day/per capita) and the FAO-FBS dataset (grams and calories/day/per capita values) were used as the unique sources currently available, in order to derive a simple yet harmonised secondary-data framework, which could serve for policy analysis and policy making therein of. Findings: The adherence to a Mediterranean-like dietary pattern outlines a general rank correlation among countries, and a broader north-south divide within Europe. Scores remain relatively stable across time. Although there has been a decrease in Mediterranean adherence in southern Europe, some central and northern European regions have seen gains. Research limitations/implications: Several data gaps do not allow a full comparison across all the indices used (i.e., lack of foodstuff detail of key-foods of the Med diet). A further problem of Med-adherence indices is that it does not consider the overall caloric intake. Practical implications: The relatively low discriminatory power of the emerging clusters of countries, reflecting the national diets- limits their usefulness in terms of policy-making recommendations. Furthermore the indices used were originally built on first-hand data (i.e., cohort studies relying on real persons), and not on aggregated mean-median values at population level (secondary data). Social implications In a period in which the interest for the health outcomes of the Mediterranean diet is on the rise in terms of preventive medicine, the P-MAI is an interesting indicator due to its user-friendliness, which allows the classification of European countries’ diets using food intake data. Originality/value: Mediterranean adherence indices may be useful as synthetic indicators for monitoring the evolution of diets and for identifying sub-regions with similar dietary patterns or changes. The P-MAI index in particular, due to its simplicity, may help to monitor the overall healthiness of national diets, and could help to inform subsequent nutrition policies, including emerging labelling provisions both at National and European level, in order to achieve public health targets (i.e., reduction of NCDs).